INDUSTRIAL-LEVEL TOTAL FACTOR PRODUCTIVITY COMPARISONS BETWEEN TAIWAN AND KOREA: 1981–2010 - Fu, Tsu-Tan; Lin, Yih-Ming; Lin, Hsing-Chun; Kong, Wen-Hsing; Chen, Po-Chun (Táiwān jīngjì yùcè yǔ zhèngcè, 2019)
The purpose of this paper is to compare the growth dynamics at the industry level between Taiwan and Korea during 1981-2010 and to identify key drivers which resulted in industrial growth. First, we concisely introduce the KLEMS approach to the growth accounting method. We estimate the industrial-level TFP using Taiwanese and Korean KLEMS databases. The empirical results show that, Taiwan's and Korea's output growth rates during 1981-1990 were higher than those of other periods. After 1990, the output growth rates slowed down for both economies. The contribution of intermediate inputs (II) accounts for majority of the gross output growth rate. The contributions of II of tertiary industries are much less than those of secondary industries. Among the intermediate inputs, material contribution is the highest in secondary industries, whereas service contribution is the highest in tertiary industries. The contribution of labor input is slight in Taiwan and Korea. Furthermore, in Taiwan, the performance of the TFP